2017
DOI: 10.1111/echo.13620
|View full text |Cite
|
Sign up to set email alerts
|

Novel echocardiographic prognostic markers for cardiac tamponade in patients with large malignant pericardial effusions: A paradigm shift from flow to tissue imaging

Abstract: Echocardiographic tissue imaging markers such as TAPSE and S are characterized by an excellent prognostic ability for development of cardiac tamponade and better prognostic value compared to routine echocardiographic signs in patients with large malignant pericardial effusion. Incorporating these markers to a recent triage pericardiocentesis score resulted in additional prognostic value and increased clinical benefit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Echocardiography is the sensitive imaging technique for detecting pericardial effusion, and it perfectly shows a large number of pericardial effusion features [ 15 ]. And chest CT also has an irreplaceable advantage in the diagnosis of pericardial cavity occupation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Echocardiography is the sensitive imaging technique for detecting pericardial effusion, and it perfectly shows a large number of pericardial effusion features [ 15 ]. And chest CT also has an irreplaceable advantage in the diagnosis of pericardial cavity occupation [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…11 Besides its utility in diagnosing PE, TAPSE has also been applied as a marker of pulmonary hypertension and, more recently, as a predictor for the development of cardiac tamponade in patients with malignant effusions. 12,13 A prior study showed that investigators trained in echocardiography could visually estimate TAPSE as normal or abnormal with good agreement. 9 However, to our knowledge, there is no prior literature examining whether emergency clinicians with a diverse level of training can accurately visually estimate TAPSE.…”
Section: Introductionmentioning
confidence: 99%